Dose Effect of Bovine Lactoferrin Fortification on Iron Metabolism of Anemic Infants - CHEN, Ke; CAO, Yanmei; DONG, Xiaobing; ZHANG, Guoying; LIU, Changqi; CHEN, Haixia; LI, Hua (Journal of Nutritional Science and Vitaminology, 2020)
To evaluate the effect of iron-fortified formula with different concentrations of bovine lactoferrin (bLF) on improvement of anemic status in term infants who were previously breast-fed. A randomized, controlled, open, and post-market intervention study. A total of 108 infants aged 6-9 mo who were previously breast-fed and weaned were selected. The subjects were divided into three groups with the sequence of outpatient: fortified group 1 (FG1) with a bLF concentration of 38 mg/100 g, FG2 with 76 mg/100 g bLF, FG0 with no bLF. The intervention duration was 3 mo. Weight, height, head circumference and the concentration of hemoglobin (Hb), serum ferritin (SF), serum transferring receptor (sTfR) were measured and sTfR-SF index (TFR-F index) and total body iron content (TBIC) were computed before and after intervention. The primary outcome measures were obtained from 96 infants (35, 33 and 28 for FG0, FG1 and FG2, respectively). After 1 mo of intervention, the changes of Hb level showed no significant difference (p>0.05) among the three groups, however, the Hb level of infants in FG2 were significantly higher than those of infants in the other two groups after 3 mo of intervention (p<0.05). The present data indicated that the formula fortified with 76 mg/100 g bLF positively affected the Hb of anemic infants who were previously breastfed when compared with fortification with 38 mg/100 g bLF and no bLF fortification.